PENINGKATAN KEMANDIRIAN MERAWAT DIRI ANAK RETARDASI MENTAL DENGAN TERAPI OKUPASI DI SDLB NEGERI LAMONGAN: Improvement of Self-Care Independence for Children with Mental Retardation Using Occupational Therapy in SDLB Negeri Lamongan - Abdul Rokhman; Fatkhur Rohmah (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2019)
Children with mental retardation depend on parents in carrying out daily activities such as in terms of self-care independence so that exercise or therapy that can be applied is occupational therapy. The purpose of this study is to determine the effect of occupational therapy on the level of self-care independence in children with mental retardation at SDLB Negeri Lamongan. The design of this study is experimental design that is quasi experimental with one group pre and post test design. The sampling technique used is non probability sampling, namely purposive sampling with a total of 15 children. Data collection was carried out using independence observation sheet. Observations were performed for 3 weeks with 5 meetings, each meeting for ? 1 hour in SDLB Negeri Lamongan. The results of the Wilcoxon sign rank test in this study showed that p value = 0.001 where p <0.05 with Z -3.411 and Z table is 1-0.0032 due to 2-sided test, the result of Z count is far from the critical number Z ± 1, 96 by moving to the left, which means that Ho is rejected, which means there is influence of occupational therapy on the level of self-care independence in children with mental retardation at SDLB Negeri Lamongan. The results of this study showed that the degree of independence of self-care before being given occupational therapy was mostly in moderate dependence category and after being given occupational therapy mostly in independent category. Occupational therapy can produce and increase independence, especially the ability in daily activities in terms of caring for themselves.